2023
DOI: 10.3389/fendo.2023.1139805
|View full text |Cite
|
Sign up to set email alerts
|

Identification and in vitro functional assessment of 10 CYP2C9 variants found in Chinese Han subjects

Abstract: Cytochrome P450 2C9 (CYP2C9) participates in about 15% of clinical drug metabolism, and its polymorphism is associated with individual drug metabolism differences, which may lead to the adverse drug reactions (ADRs). In this study, 1163 Chinese Han individuals were recruited to investigate their distribution pattern of CYP2C9 gene and find out the variants that may affect their drug metabolic activities. We successfully developed a multiplex PCR amplicon sequencing method and used it for the genetic screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…There are six key substrate regions in the P450 enzyme (Figure 2B) which are located at residues 96−117, 198−205, 233−240, 286−304, 359−369, and 470− 477, all of them were highlighted by the dashed black boxes. 30 Figure 2A is the heatmap of the DMS experimental score and our predicted score, respectively, which show a clear similar pattern of activity changes upon single-point mutations, especially in these key areas. Ordinarily, substitution close to the substrate most likely changes the enzyme activity.…”
Section: Performance On Dms Datamentioning
confidence: 76%
See 1 more Smart Citation
“…There are six key substrate regions in the P450 enzyme (Figure 2B) which are located at residues 96−117, 198−205, 233−240, 286−304, 359−369, and 470− 477, all of them were highlighted by the dashed black boxes. 30 Figure 2A is the heatmap of the DMS experimental score and our predicted score, respectively, which show a clear similar pattern of activity changes upon single-point mutations, especially in these key areas. Ordinarily, substitution close to the substrate most likely changes the enzyme activity.…”
Section: Performance On Dms Datamentioning
confidence: 76%
“…We comprehensively analyzed the saturation mutation results of P450 to demonstrate the capability of our method to design enzyme activity. There are six key substrate regions in the P450 enzyme (Figure B) which are located at residues 96–117, 198–205, 233–240, 286–304, 359–369, and 470–477, all of them were highlighted by the dashed black boxes Figure A is the heatmap of the DMS experimental score and our predicted score, respectively, which show a clear similar pattern of activity changes upon single-point mutations, especially in these key areas.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with single-SNP amplification and genotyping methods, the multiple-target region capture technology (MultipSeq Primer for the genotyping of SNP loci) based on next-generation sequencing technology is more cost-effective and has higher efficiency, enabling the simultaneous acquisition of a greater number of loci and genotyping results [ 32 , 36 , 37 ]. In the present study, by testing the 219 selected SNPs in 120 animals, it was found that three loci had a low amplification quality, seven loci presented the same genotype in all animals, and three loci were completely linked with other loci.…”
Section: Discussionmentioning
confidence: 99%
“…With the similar genotyping approach we previously established for the CYP2C9 gene (Zhang et al, 2023), one multiplex PCR amplicon sequencing and genotyping method for the CYP3A4 gene was developed in this study. The process started with an initial PCR amplification using the primers in Table 1, which enabled us to amplify multiple regions simultaneously, including the promoter, all 13 exons of the CYP3A4 gene, and the exon-intron junction areas.…”
Section: Genotypingmentioning
confidence: 99%